A novel host for Alternaria citri causing yellow leaf spot on Indian mustard (Brassica juncea L) in India - PD Meena; Pankaj Sharma; PK Rai (Journal of Oilseed Brassica, 2026)
Indian mustard (Brassica juncea L) constitutes a new host record for Alternaria citri Ellis & Pears (NFCCI 2704)fungus in India and worldwide. At the outset during 2011-12, leaves of Indian mustard (B. juncea) cultivar Varuna werefound infected with yellow leaf spots and these were also observed in succeeding years upto 2022-23 in rapeseedmustardfields in Bharatpur, India.